Tuberculosis: where and how fast are stone quarry workers infected?. (30th September 2020) - Carvalho Sousa, S; Magalhães Alves, C; Santos, S; Marques, F; Duarte, R; Gonçalves, G; Carvalho, C
Abstract: Background: In 2018 an annual tuberculosis (TB) screening program targeting stone quarry workers was implemented in two municipalities in Northern Portugal. These have been hotspots for TB (76 and 59 cases per 100 000 population per year in 2012-2016, well above the 18 cases per 100 000 population observed in Portugal in 2016), with 30% of active TB cases occurring among stone quarry workers. Screening in this setting is recommended by the World Health Organization, as exposure to silica and silicosis increase the risk of TB. Occupational health services, TB outpatient centers, the hospital, a laboratory, primary health care and public health services work closely together with employers, employees, municipal council and the community promoting meetings and continuous training. Screening activities included a symptom questionnaire, chest X-ray and sputum exam; and, after exclusion of active TB, interferon-gamma release assay (IGRA) for latent tuberculosis infection (LTBI). Preventive treatment was offered. Objective: Assess annual rate of TB infection Methods: Workers without history of TB/LTBI were IGRA tested in 2018, and retested in 2019. Annual rate of infection was calculated as the proportion of workers IGRA negative in 2018 becoming positive in 2019. Results: In 2018-2019, 274 workers were screened yearly. In 2018, 22 were diagnosed with LTBI and 26 had previous history of TB/LTBI. Out of 226 IGRA negative workers in 2018, 19 tested positive in 2019 (8.4% annual rate of infection). These individuals were not identified as close contacts of any new TB case and no cases of active TB were reported in their stone quarries. Some active TB cases were regular customers of specific bars. Conclusions: Active transmission of TB seems to be occurring among stone quarry workers. Workers that converted from IGRA negative to positive had no co-workers with active TB in the study period, suggesting they could have been infected away from the workplace, possibly in community public places. Key messages: Stone quarry workers in a high-risk TB sub-region were infected at an 8.4% annual rate, and could have been infected in community public places such as bars. Besides screening close contacts and at workplace, more efforts should be made identifying social contacts of active TB cases.